Beyond Linear: The Relationship between Corporate Social Responsibility and Market Reactions to Cross-Border Mergers and Acquisitions. Issue 3 (19th February 2022) - Shi, Jinyan; Yu, Conghui; Li, Yanxi
ABSTRACT: By combining the stakeholder theory and shareholder theory, this study examines whether corporate social responsibility (CSR) influences market reactions to cross-border mergers and acquisitions (M&A) announcements. This study employs a sample of cross-border M&A conducted by Chinese-listed companies from 2010 to 2018. We find that the impact of CSR on cumulative abnormal returns (CAR) around the announcement of cross-border M&A is not monotonically positive or negative demonstrated in previous literatures, but a nonlinear U-shaped relation. This finding shows that compared with moderate level of CSR, acquirers with extremely low or high levels of CSR realize higher CAR, indicating the complementarity of the two long competitive theories. The U-shaped relation remains across a three-step procedure significance test and several robustness tests. This study advances the debate concerning which theory best explains the effect of CSR on CAR theoretically and provides a possible explanation for the existing contradictory evidences empirically owing to ignoring the level of CSR.